The RstAB System Impacts Virulence, Motility, Cell Morphology, Penicillin Tolerance and Production of Type II Secretion System-Dependent Factors in the Fish and Human Pathogen Photobacterium damselae subsp. damselae - Terceti, Mateus S.; Vences, Ana; Matanza, Xosé M.; Barca, Alba V.; Noia, Manuel; Lisboa, Johnny; dos Santos, Nuno M. S.; do Vale, Ana; Osorio, Carlos R. (Frontiers in Microbiology, 2019)
The RstB histidine kinase of the two component system RstAB positively regulates the expression of damselysin (Dly), phobalysin P (PhlyP) and phobalysin C (PhlyC) cytotoxins in the fish and human pathogen Photobacterium damselae subsp. damselae, a marine bacterium of the family Vibrionaceae. However, the function of the predicted cognate response regulator RstA has not been studied so far, and the role of the RstAB system in other cell functions and phenotypes remain uninvestigated. Here, we analysed the effect of rstA and rstB mutations in cell fitness and in diverse virulence-related features. Both rstA and rstB mutants were severely impaired in virulence for sea bream and sea bass fish. Mutants in rstA and rstB genes were impaired in hemolysis and in Dly-dependent phospholipase activity but had intact PlpV-dependent phospholipase and ColP-dependent gelatinase activities. rstA and rstB mutants grown at 0.5 % NaCl exhibited impaired swimming motility, enlarged cell size and impaired ability to separate after cell division, whereas at 1 % NaCl the mutants exhibited normal phenotypes. Mutation of any of the two genes also impacted tolerance to benzylpenicillin. Notably, rstA and rstB mutants showed impaired secretion of a number of type II secretion system (T2SS)-dependent proteins, which included the three major cytotoxins Dly, PhlyP and PhlyC, as well as a putative delta-endotoxin and three additional uncharacterized proteins which might constitute novel virulence factors of this pathogenic bacterium. The analysis of the T2SS-dependent secretome of P. damselae subsp. damselae also led to the identification of RstAB-independent potential virulence factors as lipoproteins, sialidases and proteases. The RstAB regulon included plasmid, chromosome I and chromosome II-encoded genes that showed a differential distribution among isolates of this subspecies. This study establishes RstAB as a major regulator of virulence and diverse cellular functions in P. damselae subsp. damselae.